PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Dinniaty, Nisa Mutia; Fitriani, Dyah (Jurnal Fokus Manajemen Bisnis, 2019)
This research aims to examine the effect of job satisfaction, commitment organization and organizational culture of organizational citizenship behavior partially at PT. Telkom Indonesia Yogyakarta, this research conducted in 2 places, namely PT. Telkom Indonesia Kota Baru and PT. Telkom Indonesia Pugeran. For the distribution of questionnaires as many as 98 respondents consisting from permanent employees through two stages, namely, the first to do the distribution of validity test questionnaires of 30 respondents, and the second did the distribution of analysis test questionnaires of 68 respondents. Sampling technique in this study using Multiple Linear Regression. Validity and realibility test of the questionnaire which was used as a tool showed that the questionnare is valid and reliable for use. Test result shows the variable Job Satisfaction has a significant effect on Organizational Citizenship Behavior for PT. Telkom Indonesia. Variable Organizational Commitment has a significant effect on Organizational Citizenship Behavior for PT. Telkom Indonesia. Organizational Culture Variable significant effect on Organizational Citizenship Behavior on employees PT. Telkom Indonesia.